2009
DOI: 10.1289/ehp.0900595
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Neighborhoods: Walkability and Air Pollution

Abstract: BackgroundThe built environment may influence health in part through the promotion of physical activity and exposure to pollution. To date, no studies have explored interactions between neighborhood walkability and air pollution exposure.MethodsWe estimated concentrations of nitric oxide (NO), a marker for direct vehicle emissions), and ozone (O3) and a neighborhood walkability score, for 49,702 (89% of total) postal codes in Vancouver, British Columbia, Canada. NO concentrations were estimated from a land-use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(152 citation statements)
references
References 77 publications
9
130
1
4
Order By: Relevance
“…Nevertheless, it is generally considered that a walkable neighborhood has well mixed land use, well-connected streets, and high residential density (Saelens et al 2003;Lake et al 2010). Most researchers have adopted the integrated walkability index including just these three elements (e.g., De Meester et al 2012;Marshall et al 2009;Owen et al 2007;Leslie et al 2005;Brown et al 2009). For example, Frank and colleagues (Frank et al , 2006(Frank et al , & 2010 had constructed one of the most popular indexes including these elements.…”
Section: The Walkability Index (Wi)mentioning
confidence: 99%
“…Nevertheless, it is generally considered that a walkable neighborhood has well mixed land use, well-connected streets, and high residential density (Saelens et al 2003;Lake et al 2010). Most researchers have adopted the integrated walkability index including just these three elements (e.g., De Meester et al 2012;Marshall et al 2009;Owen et al 2007;Leslie et al 2005;Brown et al 2009). For example, Frank and colleagues (Frank et al , 2006(Frank et al , & 2010 had constructed one of the most popular indexes including these elements.…”
Section: The Walkability Index (Wi)mentioning
confidence: 99%
“…Whilst in developing countries proximity to roads is seen as providing access to transport, in the developed world those who can afford it are likely to choose living away from busy roads and traffic, with more deprived individuals tending to live in areas closer to heavy traffic and/or high traffic volumes (Marshall et al 2009). …”
Section: Exposurementioning
confidence: 99%
“…People on low incomes, in chronic ill-health, or with limited mobility may be less able to access or pay for the transport systems they need to acquire work, education and services (Jarvis and Alvanides 2008). Those on low incomes are also more likely to suffer the adverse effects of road traffic, for instance exposure to air pollution and noise (Marshall et al 2009;Namdeo and Stringer 2008;O'Neill et al 2003). Mitchell & Dorling (2003) completed a comprehensive review of UK air quality social equity studies and concluded that most studies investigating the relationship between air quality and deprivation, tended to show that air pollution is greater in more deprived communities (Mitchell and Dorling 2003).…”
Section: Introductionmentioning
confidence: 99%
“…High walkability areas were mostly located in the more densely populated city center through which residents of the suburbs are likely to commute to work. However, ozone is a secondary pollutant formed in the atmosphere rather than emitted directly from traffic exhaust, so high concentrations generally occur downwind from the high density areas; hence ozone concentrations in Vancouver where higher in the suburbs (Marshall et al, 2009).…”
Section: Observational Studiesmentioning
confidence: 99%
“…For example, larger reduction in driving would achieve greater reductions in exhaust emissions and could decrease walkers' and cyclists' risk of accident to a greater extent. However, further studies will need to take into account socio-economic status because individuals living in deprived neighborhoods are typically exposed to higher concentration of pollutants (Marshall et al, 2009;Tonne et al, 2008). Moreover, low income households and families with young children are likely to be more affected by a potential increase in the cost of food transportation caused by fuel scarcity (Kaza et al, 2011).…”
Section: The Case For Health Impact Assessment Studiesmentioning
confidence: 99%